Diretrizes estratégicas para melhoria da eficiência logística em um canteiro de obra para execução de alvenarias e revestimentos de argamassa - FALCÃO, Thiago de Faria (2010)
In civil construction, logistics can be characterized as a multidisciplinary method in the production process aimed at ensuring the design of material and human resources needed for production. Based on this fact, this work presents a methodology that seeks to characterize the processes of external masonry, sub floor, masonry and internal lining mortar, besides the relevant materials to implementation of these processes through two tools: flow charts and indicators of productivity. The first is an analytical record of the process flows described above showing the sequence of tasks performed in them, through a symbolic, aiming the optimization in terms of materials between one activity and another. The second through a model of productivity measurement and analysis of proposed specifically for the Construction Industry, which is named "Model of Factors." This research has the scope to develop a construction company building a method that aims to define the flow behavior of materials in the execution of the cases cited, and an indicator system for measuring performance for the same, with the aim of generating guidelines for improving logistics efficiency at construction sites. A general guidelines has been implemented in the process of lining mortar, providing a significant percentage drop compared the OR's daily and cumulative in two moments: before and after implementation of the guideline. This percentage rose from 126.26% to 23.07% taking into account the higher values for the two moments.